2010
DOI: 10.1136/vr.c5108
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis genotypes in Northern Ireland: herd‐level surveillance (2003 to 2008)

Abstract: Surveillance genotyping (variable number tandem repeat profiling and spoligotyping) of Mycobacterium bovis isolates from culture-confirmed bovine tuberculosis (TB)-affected herds in Northern Ireland is presented for the years 2003 to 2008 inclusive. A total of 175 M bovis genotypes were identified in 8630 isolates from 6609 herds. On average, 73 genotypes were identified each year, with 29 genotypes present in all six years. Highly significant differences (P<0.0001) were observed between the relative frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 46 publications
7
71
1
1
Order By: Relevance
“…The MIRU-VNTR characterization of this random panel of M. bovis SB0121 isolates revealed a high degree of diversity. This is consistent with previous reports from Portugal (12,13) and Italy (10) where the MIRU-VNTR type diversity of the most prevalent spoligotypes (SB0121 and SB0120, respectively) is high compared to that of the European 1 clonal complex in the United Kingdom and the Republic of Ireland (34). The underlying reasons for this high diversity in the Iberian M. bovis population remain unknown.…”
Section: Fig 1 Minimum Spanning Trees (Msts) Of the 115 Mycobacteriumsupporting
confidence: 81%
See 2 more Smart Citations
“…The MIRU-VNTR characterization of this random panel of M. bovis SB0121 isolates revealed a high degree of diversity. This is consistent with previous reports from Portugal (12,13) and Italy (10) where the MIRU-VNTR type diversity of the most prevalent spoligotypes (SB0121 and SB0120, respectively) is high compared to that of the European 1 clonal complex in the United Kingdom and the Republic of Ireland (34). The underlying reasons for this high diversity in the Iberian M. bovis population remain unknown.…”
Section: Fig 1 Minimum Spanning Trees (Msts) Of the 115 Mycobacteriumsupporting
confidence: 81%
“…These studies showed that high levels of discrimination could be achieved by spoligotyping (discriminatory index [D] ϭ 0.89 and 0.87 in Portugal and Spain, respectively), although subsequent studies from Portugal found that discrimination actually increased with MIRU-VNTR typing (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Herd size has been found to be a significant risk factor for bTB disclosure and herd breakdown risk in a number of studies (Brooks-Pollock and Keeling, 2009;Byrne et al, 2014;Doyle et al, 2014;Skuce et al, 2010). Herd size may contribute to increased bTB risk due to the potential for increased residual infection, especially if tests can behave differentially across herd sizes.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…The NI cut-off is more stringent interpretation using a lower optical density threshold (PPDB-PPDA OD = 0.05 if PPDB OD ≥ 0.1), increasing the sensitivity of the test, but reducing the specificity of the test in comparison to the commercial test cut-off (OD = 0.1). (Roring et al, 2000;Skuce et al, 2010).…”
Section: Ante-mortem Testingmentioning
confidence: 98%